2014
DOI: 10.1093/bioinformatics/btu557
|View full text |Cite
|
Sign up to set email alerts
|

A novel feature-based approach to extract drug–drug interactions from biomedical text

Abstract: The source code is available for academic use at http://www.biosemantics.org/uploads/DDI.zip.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…Another study to extract information on drug-drug interactions (DDI) from biomedical text was proposed by Bui et al [3]. DDI pairs are mapped according to their syntactic structure followed by the generation of feature vectors for these DDI pairs.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study to extract information on drug-drug interactions (DDI) from biomedical text was proposed by Bui et al [3]. DDI pairs are mapped according to their syntactic structure followed by the generation of feature vectors for these DDI pairs.…”
Section: Related Workmentioning
confidence: 99%
“…DDI pairs are mapped according to their syntactic structure followed by the generation of feature vectors for these DDI pairs. These feature vectors are then used for the generation of a predictive model which classify the drug pair as interacting or not interacting [3].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, [13] demonstrated that partitioning candidate DDI pairs based on their syntactic properties then using specific group of features for each partition improves the performance of the DDI extraction system. Following this strategy, we classify candidate pairs into different groups based on their positions into the sentence.…”
Section: ) Candidate Drug Pairs Partitioningmentioning
confidence: 99%
“…Trigger_DRUG_Position features: Like Bui et al [13] we determine the relative position of each trigger word within the phrase by checking the following cases:…”
Section: B) One-drug Featuresmentioning
confidence: 99%